Advances in Service Quality Measurement: Insights from Higher Education - Arif Fakhrudin; Maria Valeria Roellyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify and analyse the dimensions of higher education service quality that have evolved globally within the context of higher education institutions. Research on service quality has progressed from the SERVQUAL framework to the emergence of alternative models that are adapted to the unique conditions of higher education. By examining service quality in this sector, valuable insights can be obtained regarding institutional performance and the level of student satisfaction. This study employs a systematic literature review of international publications sourced from reputable databases (Emerald, Wiley, Springer, Taylor & Francis, and Sage Publishing) to capture global trends in the conceptualization of service quality dimensions in higher education. The analysis reveals six major conceptual developments of measurement models, formulated under various acronyms, with the seven-dimension model appearing most frequently, particularly in the Emerald database. Most of these developments represent evaluations and adaptations of earlier frameworks. The findings highlight the need for further research to establish more authentic conceptual dimensions that reflect the distinctive characteristics of higher education while integrating a broader perspective from multiple service stakeholders.